2017
DOI: 10.3390/atmos8100203
|View full text |Cite
|
Sign up to set email alerts
|

The Peñalara Mountain Meteorological Network (1999–2014): Description, Preliminary Results and Lessons Learned

Abstract: This work describes a mountain meteorological network that was in operation from 1999 to 2014 in a mountain range with elevations ranging from 1104 to 2428 m in Central Spain. Additionally, some technical details of the network are described, as well as variables measured and some meta information presented, which is expected to be useful for future users of the observational database. A strong emphasis is made on showing the observational methods and protocols evolution, as it will help researchers to underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…saihhebro.com. We also used an SD sensor in the Central System mountain range (Durán et al, 2017), which is from the National Meteorological Agency of Spain (AEMET). We projected the meteorological variables from the WRF simulation to elevations of the different telenivometers for simulations.…”
Section: Validation Proceduresmentioning
confidence: 99%
“…saihhebro.com. We also used an SD sensor in the Central System mountain range (Durán et al, 2017), which is from the National Meteorological Agency of Spain (AEMET). We projected the meteorological variables from the WRF simulation to elevations of the different telenivometers for simulations.…”
Section: Validation Proceduresmentioning
confidence: 99%
“…La Herrería tower is part of the Guadarrama Monitoring Network (GuMNet, GuMNet (2018)), which aims at providing observational meteorological and climatological records to deepen into scientific research in the mountainous area of Sierra de Guadarrama (Durán et al, 2018). We record data from aspirated thermometers, cup anemometers, a wind vane and IRGASON devices among others in a 10-m high fixed tower.…”
Section: Data: Meteorological Observationsmentioning
confidence: 99%
“…The latter is closely linked to the turbulent characteristics of the stable boundary layer (SBL) and the variability of CO 2 . Several external factors have been documented to affect these downslope winds: the steepness of the slope and the distance to the mountain range (Horst and Doran, 1986), the canopy layer (Sun et al, 2007), spatial variations in soil moisture (Banta and Gannon, 1995;Jensen et al, 2017) and the direction and intensity of the synoptic wind (Fitzjarrald, 1984;Doran, 1991). However, most of the investigations analysing the influence of those external factors are carried out using numerical simulations, and there is a lack of observational studies to validate them.…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, Sastre et al (2015) showed with a numerical experiment at contrasting sites that soil-moisture differences do not affect the afternoon and evening transition values with the same intensity but depend on the site. With respect to the background flow, by using a one-dimensional model, Fitzjarrald (1984) observed that the onset time of katabatic winds is affected by the retarding effect of the opposing synoptic flow and reduced cooling rates. Jiménez et al 2019found that moderate background winds in the direction of the thermally driven flow enhance the latter by adding a dynamical component.…”
Section: Introductionmentioning
confidence: 99%